Persistence of the Deficit Model in Japan's Science Communication: Analysis of White Papers on Science and Technology. Issue 3 (1st September 2017) - Ishihara-Shineha, Seiko
Abstract : Given the Great East Japan Earthquake in 2011, Japan is at a major point to reevaluate its policies on the public communication of science. However, the government's self-reflection on their measures and policies of science communication has been inadequate. This study reviewed and analyzed descriptions of science-related public communication in the successive Japanese white papers on science and technology (S&T) from 1958 to 2015 with quantitative-qualitative hybrid approaches. Traditional enlightenment activities have always been given higher priority, even after the S&T Basic Plan aimed at two-way science communication, and have used such justifications as "the shying-away of young people from S&T, " "accountability for research investment, " and "problem-solving on issues related to S&T and society, " without considering the reality of science communication.